On the dynamics of persistently degassing volcanoes from new physics-based approaches - Girona, Társilo (2015)
Persistently degassing volcanoes are the most active sub-aerial volcanoes around the world. Their activity consists of passive degassing periods interspersed by eruptions every few months or years. I present three new physics-based studies that unravel the underlying dynamics of these volcanoes. First, I calculate the pressure changes induced by the gas release during quiescence. A key finding is that magma reservoirs can depressurize several MPa within the inter-eruptive timescales, which suggests that passive degassing can induce unrest episodes and eruptions. Second, I develop a method to monitor the high-frequency water vapor emissions using light scattering theory and analysis of digital images. I show that degassing of Erebus and Mayon volcanoes emerges as a fractal phenomenon. Third, I simulate the bubble dynamics of volcanic conduits to investigate the processes leading to phreatic eruptions. I found that they can be preceded by amplitude and frequency shifts in the gas emission time series. These studies give new insights on the dynamics of persistently degassing volcanoes, and help to improve the monitoring and interpretation of degassing time series.